2016
DOI: 10.1039/c6gc00581k
|View full text |Cite
|
Sign up to set email alerts
|

Pervaporation-assisted catalytic conversion of xylose to furfural

Abstract: A reactor/membrane system was designed, built, and tested for improved furfural production from xylose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…At present, the rapidly depleting fossil fuels and escalating energy consumption coupled with rising environmental awareness among nations have led to an increased focus on alternative, viable, ecofriendly, and renewable energy sources. Biomass has considered by experts as the only truly sustainable source of energy and organic carbon for our industrial society, and it has the potential to displace petroleum for the production of chemicals and liquid transportation fuels …”
Section: Introductionmentioning
confidence: 99%
“…At present, the rapidly depleting fossil fuels and escalating energy consumption coupled with rising environmental awareness among nations have led to an increased focus on alternative, viable, ecofriendly, and renewable energy sources. Biomass has considered by experts as the only truly sustainable source of energy and organic carbon for our industrial society, and it has the potential to displace petroleum for the production of chemicals and liquid transportation fuels …”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the average permeability of 2‐furaldehyde differed at least three orders of magnitude between LDPE and EVOH. According to Wang, Balsara, and Bell, the block copolymer polystyrene‐block‐polydimethylsiloxane‐block‐polystyrene (SDS) had twice as high 2‐furaldehyde permeability as that of cross‐linked polydimethylsiloxane (PDMS) despite in such a small volume fraction of the transporting block. In this regard, having more permeable transporting block copolymers or cross‐linked structures will increase film resistance to permeation by 2‐furaldehyde .…”
Section: Resultsmentioning
confidence: 99%
“…These membranes were received as sheets and were cut to fit the membrane cell. The block copolymer polystyreneblock-polydimethylsiloxane-block-polystyrene (SDS), which was previously shown to be permeable to furfural, [38][39][40] was purchased from Polymer Source and was used as received. The number-averaged molecular weight of the polydimethylsiloxane block was 104 kg mol −1 , and that of each polystyrene block was 22 kg mol −1 .…”
Section: Experimental Methodsmentioning
confidence: 99%
“…30,31,41 This study builds on our previous investigations, which demonstrated the performance of a batch membrane reactor for producing furfural from xylose using a hetero-geneous catalyst. 40 Here, we combine the reaction and membrane processes thereby eliminating the extraneous heating and cooling elements of the prior membrane reactor design in order to achieve a system that can be used for continuous reaction and separation. We found that pervaporation is able to fully retain the homogeneous catalyst in the reactor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation